IMMUNOLOGICAL CHARACTERISTICS OF THE ENDOMETRIUM IN WOMEN WITH IMPAIRED FERTILITY (Modern education and development, 2025)
The main morphological criterion of chronic endometritis is the presence of inflammatory infiltrates consisting mainly of lymphoid elements and plasma cells with focal or diffuse location in the stroma and glands. Immunological research allows to evaluate the phenotypic composition of endometrial cells, identify the number of cytotoxic cells that limit embryo implantation and contribute to reproductive dysfunction, and determine the need for complex therapy.